The Role of 'Aisyiyah Ranting Kemasan In the Development of Religious Education for Women - Anastasya, Jasmine Malya; Azani, Mohammad Zakki (Universitas Muhammadiyah Surakarta, 2025)
This research aims to analyze Islamic science for women and the social construction of women's religious education in Packaging village, examining the implementation of religious education programs organized by 'Aisyiyah Ranting Kemasan, and examine its contribution and impact on increasing women's awareness. This study uses a qualitative approach with an exploratory descriptive design. Data was collected through participatory observation, in-depth interviews with 'Aisyiyah administrators and members and documentation studies, then analyzed using Miles and Huberman's interactive model which included data reduction, data presentation and conclusion drawn, with data validity strengthened through source triangulation. The results of the study show that the limited participation of women in religious education is not caused by low interest in learning, but by social construction, domestic burden, and lack of social support. Community-based religious education managed by 'Aisyiyah through Qur'anic tahsin activities, routine recitation and contextual Islamic studies has been proven to be able to expand access to religious education for village women. The program has an impact on increasing religious understanding, women's confidence, and strengthening women's social solidarity. This study confirms that community-based Islamic religious education managed by women's organizations such as 'Aisyiyah has a strategic role as an instrument for women's empowerment and strengthening Islamic science in the context of rural communities.